A novel therapy with zoledronic acid of bone metastasis in advanced prostate cancer reflecting molecular investigations - Oborska, Sylwia; Bodnar, Lubomir; Szarlej-Wcisło, Katarzyna; Szczylik, Cezary (Contemporary Oncology/Współczesna Onkologia, 2006)
Prostate cancer continues to represent a major therapeutic challenge. There is still observed a large number of patients worldwide. This malignancy is mainly diagnosed in industrialized countries. Dietary factors, lifestyle – related factors, and androgens have long been recognized as contributors to the risk of prostate cancer. During the last 10 years, molecular studies have provided unexpected molecular events showing the prostate cancer tumorigenesis and progression. The modern therapy of prostate cancer relies on hormonal therapy. One step further for treatment of androgen-independent prostate cancer means chemotherapy based upon docetaxel, estramustine, and glucocorticoids. Bone metastases are frequent in prostate cancer. One of the drawbacks of long-term hormone therapy has been reported in recent studies as the changed bone metabolism. Long-term treatment of zoledronic acid is safe and gives substantial clinical benefits for men with metastatic hormone-refractory prostate cancer. The huge challenge still exists to seek novel agents which will offer better results in the course of the entity. Imatinib is a well-known agent blocking the function of protein kinases, and one of them is associated with PDGF (platelet-derived growth factor) receptor. The latter could become a target in the treatment of prostate cancer. Vitamin D and its metabolites may improve results of chemotherapy used to control prostate cancer.